Rekomendasi Pemupukan K Spesifik Lokasi untuk Tanaman Padi Sawah - I Made Adnyana (Jurnal Agrista, 2006)
Recommendation of Potassium Fertilizer Site Specific for Rice PlantABSTRACT. Fertilizer use efficiency is changing greatly depending on soil properties, fertilizer type, irrigation and level of intensive cultivation. A site specific potassium (K) experiment was conducted to formulate the fertilizer recommendation of K for rice plant in different K soil status. The objective of this research were to select a proper soil test method, classify the soil test value of K into two or more classes and fertilizer recommendation of K to rice plant. In this study it was found that the method of NH4OAc 1N pH 7 was the best technique for soil analysis. Based on the method, there are 3 available classes of K i.e. low, medium, and high. The soil with the highest availability of K does not require fertilizing with K, because it has been fulfilled by the water irrigation and straw. The fertilizer recommendation of K for rice plant at medium class is less than low class.